Mitochondrial DNA haplogrouping of the brown bear, Ursus arctos (Carnivora: Ursidae) in Asia, based on a newly developed APLP analysis. (23rd January 2014) - Hirata, Daisuke; Abramov, Alexei V.; Baryshnikov, Gennady F.; Masuda, Ryuichi
<x xml:space="preserve">Abstract</x> Sequence analyses of the complete brown bear, Ursus arctos, mitochondrial DNA (mtDNA) genome have detected scattered single nucleotide polymorphisms (SNPs) that define distinct mtDNA haplogroups in phylogeographical studies. The degraded DNA in historical samples, such as stuffed or excavated specimens, however, is often not suitable for sequence analyses. To address this problem, we developed an amplified product length polymorphism (APLP) analysis for mtDNA‐haplogrouping U. arctos specimens by detecting haplogroup‐specific SNPs. We verified the validity and utility of this method by analysing up to 170‐year‐old skin samples from U. arctos specimens collected widely across continental Eurasia. We detected some of the same haplogroups as those occurring in eastern Hokkaido (Japan) and eastern Alaska in continental Eurasia (the Altai and the Caucasus). Our results show that U. arctos in eastern Hokkaido and eastern Alaska descended from a common ancestor in continental Eurasia, and suggest that U. arctos occupied several refugia in southern Asia during the Last Glacial Maximum. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 627–635.